The Effect of the Implementation of PSAK 73 (Leases) and Good Corporate Governance on the Quality of Financial Statements, with Company Size as a Control Variable - Wahyu Hidayatulloh; Eni Srihastuti; Marhaendra Kusuma (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to examine the impact of Good Corporate Governance (GCG) and the implementation of PSAK 73 on the quality of financial statements in transportation sector companies listed on the Indonesia Stock Exchange from 2022 to 2024. The control variable for this analysis is firm size. A quantitative methodology based on the causality approach was used in this study. Eleven companies were randomly selected using purposive sampling; a total of 33 observations were made. Multiple linear regression was used to analyze the data. According to the study’s findings, financial statement quality is positively and significantly influenced by the implementation of PSAK 73. Financial reporting quality is also significantly influenced by institutional ownership and managerial ownership, which serve as proxies for GCG. Financial reporting quality is significantly influenced by the simultaneous implementation of PSAK 73 and GCG, with firm size as a control variable. The findings of this study indicate that better financial reporting can be achieved through the implementation of corporate governance procedures and accounting standards.